Lexical decomposition of English prepositions and their fusion with verb lexical classes in motion constructions - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Ignasi Navarro i Ferrando Universitat Jaume I, Spain   ABSTRACT In this paper, we firstly present a tentative formalization of a Lexical Template (LT) and a meta-language for spatial particle semantics within the framework of the Lexical Constructional Model (LCM). The semantic module consists of a set of Lexical Functions, which operate on a semantic primitive in order to produce a hyponym by elaborating topological, dynamic and functional information. The syntactic module expresses situations (positions or states) plus the argument structure. Secondly, we illustrate and discuss several LTs with the purpose of exploring spatial particle subsumption constraints with constructions such as caused motion and intransitive motion, as well as the types of verbal Aktionsart that might fuse with them. The COCA is used as a data source. We conclude that spatial particles contribute meaning to the extent that they partially determine the type of Aktionsart of the verb licensed by the motion construction.